(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research deals with the issue of (characterizing the principles of jurisprudence in terms of definitive and presumptive) between two great scholars of the Al-Maqasediya School; Imam Al-Shatibi and Sheikh Al-Taher bin Ashour, may Allah Almighty have mercy on them, through their two books Al-Muwafaqat fi Usul Al-Shari’a, and the Intentions of Islamic Shari’a. The researcher tried to root the issue in the view of the fundamentalists, then presented the opinions of the two Scholars, supported by evidences for each of them from their aforementioned sources, and then discussed each of the two sayings with what appeared to me based on analysis first, and on the sources approved in the principles of jurisprudence, then arriving at the most correct opinion of not stipulating Peremptory issues of jurisprudence and its evidences.